1983
DOI: 10.1002/anie.198302831
|View full text |Cite
|
Sign up to set email alerts
|

Proximity Effects in Organic Chemistry—The Photoelectron Spectroscopic Investigation of Non‐Bonding and Transannular Interactions

Abstract: Classical structural formulas often convey the impression onb those relationships between the atoms are of importance which hold a molecule together as symbolized by the chemical bonds. However, many interactions between atoms or groups of atoms are not adequately denoted in this manner. Nevertheless, their existence can have important consequences for ground state energies (cis-difluoroethylene is more stable than trans-difluoroethylene), conformations (the syn form of methyl vinyl ether is more stable than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
1

Year Published

1984
1984
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(54 citation statements)
references
References 467 publications
(1 reference statement)
1
40
1
Order By: Relevance
“…We also found that this method using 5-arylcarbonyl-4-ethoxycarbonylmethyl-3-(1-pyridinio)thiophene-2-thiolates as key intermediates is much more effective than those described earlier by us [2][3][4] and is widely applicable to the preparation of various 3-alkylthio-and 3-(benzylthio)thieno [3,4-b]indolizine derivatives. To the best of our knowledge, the intramolecular arene-arene interaction through a highly flexible spacer such as the sulfide bond is scarcely reported, 5,6) and if its conformational control is possible through such interaction, these molecules might be used as low energy molecular switches and chiral auxiliaries. 7,8) For the staggered conformations in relation to the sulfide spacer in 3-(benzylthio)thieno [3,4-b]indolizine derivatives, there are two gauche (G1, G2) and one anti form.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We also found that this method using 5-arylcarbonyl-4-ethoxycarbonylmethyl-3-(1-pyridinio)thiophene-2-thiolates as key intermediates is much more effective than those described earlier by us [2][3][4] and is widely applicable to the preparation of various 3-alkylthio-and 3-(benzylthio)thieno [3,4-b]indolizine derivatives. To the best of our knowledge, the intramolecular arene-arene interaction through a highly flexible spacer such as the sulfide bond is scarcely reported, 5,6) and if its conformational control is possible through such interaction, these molecules might be used as low energy molecular switches and chiral auxiliaries. 7,8) For the staggered conformations in relation to the sulfide spacer in 3-(benzylthio)thieno [3,4-b]indolizine derivatives, there are two gauche (G1, G2) and one anti form.…”
mentioning
confidence: 99%
“…Found: C,58.47;H,3.24;N,thieno [3,4-b]indolizine-9-carboxylate (7p): 66% (from 4a and 4-cyanobenzyl bromide (5f) 3.61;N,5.28. Found: C,63.37;H,3.85;N,5.00.…”
mentioning
confidence: 99%
“…However, orbital proximity effects in rigid systems are well documented (22) and through space interactions of oxygen lone pair orbitals are known to influence conformer populations (23). These concepts are being applied to the synCan.…”
Section: Resultsmentioning
confidence: 99%
“…Methyl 5-(spiro [2.4]heptn-4,6-die11-I-yl)penranonte (22) Utilizing the analogous basic elimination procedure outlined above the acetate 20 was converted to the triene 22. This triene 22 was recovered unchanged after 65 h at 195'C in a sealed tube in toluene; ir (film): 1727 (C=O), 1662 (C=C) cm-I; 'H nmr (CCI,) (23) Isovaleraldehyde (1.0 g, 9.8 mmol, Aldrlch) In dichloromethane (15 mL) was added to a tetrahydrofuran solut~on (I5 mL) containing methyl(triphenylphosphoryl~dine)acetate (3.6 g, 10 8 mmol.…”
Section: Methyl 4-isopropyl-3-hydroxy-5-(spiro[24]hep~46-dien-i -Yl)-mentioning
confidence: 99%
“…[1, [24][25][26] Some may object that carotenoids with norbornadiene and polyketone rings are no longer omniconjugated [27] and therefore should not be compared with those compounds with full conjugation between all connected moieties. However, most chemists will classify the compounds shown in part a of Scheme 1 as carotenoids doped with permissible auxochromes.…”
Section: Introductionmentioning
confidence: 99%